First make an equation for her purchase. 5 bracelets $3 each = $15. the total is 36 since she pays $40 and gets $4 back, 40-4=36. 3 can represent the 3 necklaces and x is the price of each (3x).
Here's our equation: 3x+15=36
Now solve: First subtract 15 from both sides of the equation to keep it balanced and to separate the variable from the constants.
3x+15-15=36-15
3x=21
Next divide both sides by 3.
3x/3=21/3
x=7
You can check if this is right by going back to the word problem. 3 bracelets $5 each = 15. 3 necklaces $7 each = 21. 21+15=36. If she pays $40, 40-36-= $4 in change.
Each necklace is $7